(untitled) (Medico Legal Update, 2020)
Objectives: The study aimed to evaluate the effectiveness of the physical activities program for the elderly among the quality of life; to determine association between elderly life qualities with their socio-demographic data. Method: A quasi experimental design was carried out from 14th January 2019, to 20th September 2019 in the city of Al-Amara. A random sample was used to select 6 out of 14 primary health care centers. A purposive sample was used through inclusion and exclusion criteria include (50) elderly visiting health centers for therapeutic or preventive reasons. The collected sample was divided equally (25) into two groups of men and women (study and control group) while the first group underwent an activity program. The data of the study were collected through the interview method and using the designed tool which contained (3) parts. Results: The findings of the study show that the two groups have a low level of activity and quality of life for the elderly before the program is conducted, while after the implementation of the program, the study group showed a significant improvement in physical activities at a high level score (2.36± 0.209), while the control group stay in same level score (1.37± 0.183). Quality of life demonstrated very good level score for post–test in the study group (3.91± 0.436) more than control group (1.73± 0.203).